Generative Artificial Intelligence In The EFL Context: Insights From The Higher Education Sector - Faizin, Halim Ahmad; Sutantohadi, Alief; Noviabahari, Jannatul Laily; Permatasari, Ita (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This qualitative study aims to gain insights into how English lecturers perceive and integrate generative Artificial Intelligence (AI) in their teaching, an increasingly relevant topic in education. Guided by the Technology Acceptance Model (TAM), the research involved two lecturers from a higher education context. Findings reveal a shift in perception: although both participants were initially reluctant due to unfamiliarity and concerns about learning quality, they gradually embraced AI after firsthand experience. They now recognize its potential to support teaching while maintaining careful oversight to ensure it does not compromise the learning process. Their evolving views highlight the importance of adaptability and critical awareness in incorporating AI into English language education.